The Effectiveness of Herbal Therapy with Boiled Bay Leaves on Uric Acid Levels in Gout Patients at the Abang II Community Health Center - Ni Kadek Krisna Candra Dewi; Ni Putu Diwyami; Ni Luh Kade Wiradani (Cleanliness: Journal of Health Sciences and Medical Research, 2026)
Gout is one of the metabolic disorders that commonly occurs in society, caused by high levels of uric acid in the blood (hyperuricemia). This condition can cause joint pain that interferes with daily activities so that it can reduce the quality of life of the sufferer. One potential non-pharmacological treatment alternative is the administration of bay leaf (Syzygium polyanthum) boiled water. Bay leaves contain flavonoids, tannins, and essential oils that are known to be able to lower uric acid levels naturally and effectively. This study aims to determine the effectiveness of giving bay leaf boiled water on reducing uric acid levels in hyperuricemia patients in the working area of the Abang II Health Center. This study uses a pre-experimental design with a one group pre-test and post-test design. A total of 8 samples were selected using the convenience sampling technique. The intervention carried out was by giving bay leaf boiling water twice a day for seven days. Uric acid levels were measured before and after the intervention using a GCU (Glucose Cholesterol Uric Acid) digital tool. The results of Wilcoxon's statistical test showed a significant decrease in uric acid levels after therapy p=0,011 (p < 0.05). The conclusion of this study is that bay leaf decoction is effective as a complementary therapy to reduce uric acid levels, and can be an alternative natural treatment that is cheap and has minimal side effects for the community.